2022
DOI: 10.1111/febs.16599
|View full text |Cite
|
Sign up to set email alerts
|

Core fucose‐specific Pholiota squarrosa lectin (PhoSL) as a potent broad‐spectrum inhibitor of SARS‐CoV‐2 infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike protein (S protein) is highly N‐glycosylated, and a “glycan shield” is formed to limit the access of other molecules; however, a small open area coincides with the interface to the host's receptor and also neutralising antibodies. Most of the variants of concern have mutations in this area, which could reduce the efficacy of existing antibodies. In contrast, N‐glycosylation sites are relatively invariant, and some are essential for infection. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…Cyanovirin-N, a lectin produced by the cyanobacterium Nostoc ellipsosporum , binds to gp120, a protein on the HIV envelope, and inhibits HIV infection by HIV membrane fusion 33 , 34 . Recently, it was reported that PhoSL inhibits SARS-CoV-2 infection by binding to S protein, a protein on the SARS-CoV-2 envelope 35 . We found that PhoSL inhibited HBV infection of HepG2-hNTCP-C4 FUT8 KO cells, which cannot bind PhoSL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanovirin-N, a lectin produced by the cyanobacterium Nostoc ellipsosporum , binds to gp120, a protein on the HIV envelope, and inhibits HIV infection by HIV membrane fusion 33 , 34 . Recently, it was reported that PhoSL inhibits SARS-CoV-2 infection by binding to S protein, a protein on the SARS-CoV-2 envelope 35 . We found that PhoSL inhibited HBV infection of HepG2-hNTCP-C4 FUT8 KO cells, which cannot bind PhoSL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HM‐specific lectins from plants or marine red algae have been shown to inactivate (neutralize) SARS‐CoV‐2 10–15 . Regarding core fucose‐specific lectins, Yamasaki et al 34 recently reported the neutralization of SARS‐CoV‐2 by a mushroom Pholiota squarrosa –derived core fucose‐specific lectin.…”
Section: Discussionmentioning
confidence: 99%
“…HM-specific lectins from plants or marine red algae have been shown to inactivate (neutralize) SARS-CoV-2. [10][11][12][13][14][15] Regarding core fucose-specific lectins, Yamasaki et al 34 recently reported the neutralization of SARS-CoV-2 by a mushroom Pholiota squarrosa-derived core fucose-specific lectin. However, OAA, which was found to bind to SARS-CoV-2 in column experiments, showed no neutralizing activity.…”
Section: Discussionmentioning
confidence: 99%
“…PhoSL is a trimeric non-tandem repeat lectin with a fold akin to β-prism II lectins ( Yamasaki et al. 2019 , 2023 ). Interestingly, some PhoSL homologs, such as SL2-1 from the bacterium Streptomyces rapamycinicus ( Vainauskas et al.…”
Section: Classification Of Tandem-repeat Lectinsmentioning
confidence: 99%